A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Synthetic biology for sustainable food colourant production: Innovations and opportunities - Bingyin Peng; Ali Jahanian; Thomas R. Collier; Huadong Peng; James B. Behrendorff; Robert E. Speight (Food Chemistry, 2026)

Visualization-based evaluation of short-chain PFAS effects on ABCG2 in human cell models: A preliminary study - Gracen E. Collier; Ramon Lavado (Next Research, 2025)

How Do We Know What We Know About Consumer Attitudes Towards Meat Sustainability? A Scoping Review of Studies Published Globally Between 2010–2022 - Cecilia Msogoya; Jennifer J. Otten; Clair E. Werch; Olivia Meader Yetter; Elizabeth Abraham; Hannah McKinley; Charlotte Wolfert; Sarah M. Collier; Marie L. Spiker (Current Environmental Health Reports, 2025)

The seven sins of climate change: A review of rates of change, and quantitative impacts on ecosystems and water quality in the Great Barrier Reef - Katharina E. Fabricius; Aimee Brown; Catherine Collier; Mari-Carmen Pineda; Barbara Robson; Sven Uthicke; Jane Waterhouse (Marine Pollution Bulletin, 2025)

Pharmaceutical Sciences: Insights and Observations from Academic Chairs and Vice Chairs - Kristy M. Ainslie; Albert A Bowers; Robert H. Chichewicz; Lara S. Collier; Jonathan A. Doorn; Christopher R. Frei; Hamidreza Ghandehari; Robert B. Gibbs; David S. Lawrence; Craig R. Lee; Donald E. Mager; Paul Marker; et al. (The AAPS Journal, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

An in-depth examination of Per- and Polyfluoroalkyl (PFAS) effects on transporters, with emphasis on the ABC superfamily: A critical review - Gracen E. Collier; Ramon Lavado (Toxicology, 2024)

Expanding the Food Agency Framework: A Mixed Methods Research Exploring Facilitators and Barriers to Home Meal Preparation Behavior in Urban and Rural Virginia Population - J. Yi; A. Stewart; N. Porter; D. Cladis; E. Collier; B. Davy; J. Lahne (Journal of the Academy of Nutrition and Dietetics, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Estimating angler effort and catch from a winter recreational fishery using a novel Bayesian methodology to integrate multiple sources of creel survey data - Caroline M. Tucker; Simone Collier; Geoffrey Legault; George E. Morgan; Derrick K. de Kerckhove (Fisheries Research, 2024)

Heritable differences in abundance of bacterial rhizosphere taxa are correlated with fungal necrotrophic pathogen resistance - Cloe S. Pogoda; Kyle G. Keepers; Stephan Reinert; Zahirul I. Talukder; Brian C. Smart; Ziv Attia; Jason A. Corwin; Kennedy L. Money; Erin C. E. Collier‐zans; William Underwood; Thomas J. Gulya; C. Alisha Quandt; et al. (Molecular Ecology, 2024)
Host–microbe interactions are increasingly recognized as important drivers of organismal health, growth, longevity and community‐scale ecological processes. However, less is known about how genetic variation affects hosts' associated microbiomes and downstream phenotypes. We demonstrate that sunflower ( Helianthus annuus ) harbours substantial, heritable variation in microbial communities under field conditions. We show that microbial communities co‐vary with heritable variation in resistance to root infection caused by the necrotrophic pathogen Sclerotinia sclerotiorum and that plants grown in autoclaved soil showed almost complete elimination of pathogen resistance. Association mapping suggests at least 59 genetic locations with effects on both microbial relative abundance and Sclerotinia resistance. Although the genetic architecture appears quantitative, we have elucidated previously unexplained genetic variation for resistance to this pathogen. We identify new targets for plant breeding and demonstrate the potential for heritable microbial associations to play important roles in defence in natural and human‐altered environments.

Timing is everything; operational changes at a pumping station with a gravity sluice to provide safe downstream passage for silver European eels and deliver considerable financial savings - Liam J. Carter; Rosalind M. Wright; Robert E. Thomas; Jake Reeds; Leona A. Murphy; Stephen J. Collier; Oliver Evans; Henrik Baktoft; Jonathan D. Bolland (Journal of Environmental Management, 2023)

Differences in body image, but not portion size, in response to seeing images of ideal vs average body shapes in males - Jennifer Gatzemeier; Chloe Balaam; Amy Collier; Anna McAnallen; Gemma Fox; Aimee E. Pink; Menna Price (Appetite, 2023)

A new deglacial climate and sea-level record from 20 to 8 ka from IODP381 site M0080, Alkyonides Gulf, eastern Mediterranean - Ilaria Mazzini; Thomas M. Cronin; Robert L. Gawthorpe; Richard E. Ll Collier; Gino de Gelder; Anna Rose Golub; Michael R. Toomey; Robert K. Poirier; Huai-Hsuan May Huang; Marcie Purkey Phillips; Lisa C. McNeill; Donna J. Shillington (Quaternary Science Reviews, 2023)

The influence of passive wedge-wire screen aperture and flow velocity on juvenile European eel exclusion, impingement and passage - Liam J. Carter; Stephen J. Collier; Robert E. Thomas; Josh Norman; Rosalind M. Wright; Jonathan D. Bolland (Ecological Engineering, 2023)

Some like it hot: Temperature and hydrodynamic factors influence Xenobalanus globicipitis attachment to cetaceans - Milan M. Dolezal; Vivienne Foroughirad; Frank E. Fish; Ann‐Marie Jacoby; Melissa A. Collier; Colin J. Murphy; Keith A. Rittmaster; Janet Mann (Marine Mammal Science, 2023)
Barnacles can reveal much about the physiology, health, and spatial ecology of their cetacean hosts. Here, we examine how temperature and hydrodynamic factors impact presence of Xenobalanus globicipitis , a pseudo‐stalked barnacle that attaches exclusively to cetaceans. We hypothesized that temperature is a key environmental factor (i.e., water temperature) and physiological factor, in that X. globicipitis prefers the warmest skin temperature for attachment, possibly as a mechanism for survival in colder waters. First, we demonstrate a global relationship between spatial ecology of host species and presence of X. globicipitis . Notably, X. globicipitis is absent in the four species occupying waters with the lowest sea surface temperature (SST) year‐round, but present in migratory species that likely acquire the barnacle in waters with higher SST. Second, barnacle attachment location on common bottlenose dolphin ( Tursiops truncatus ) dorsal fins corresponds with fin temperature and hydrodynamics. Although body temperature may influence attachment location on the body of the animal, hydrodynamic forces, as previously proposed, determine how well barnacles can remain attached during the adult stage. X. globicipitis prevalence likely provides important bioindicator, ecological, and physiological information about its host. As parasitic infestation has some cost, these results have implications for cetacean health in warming seas.

How consistent is the advice from stock assessments? Empirical estimates of inter‐assessment bias and uncertainty for marine fish and invertebrate stocks - Rujia Bi; Chip Collier; Roger Mann; Katherine E. Mills; Vincent Saba; John Wiedenmann; Olaf P. Jensen (Fish and Fisheries, 2023)
Fishery management frequently involves precautionary buffering for scientific uncertainty. For example, a precautionary buffer that scales with scientific uncertainty is used to calculate the acceptable biological catch downward from the overfishing limit in the US federal fishery management system. However, there is little empirical guidance to suggest how large buffers for scientific uncertainty should be. One important component of uncertainty is variation among different assessments of the same stock in estimates of management‐relevant quantities. We analysed commercially exploited marine fish and invertebrate stocks around the world and developed Bayesian hierarchical models to quantify inter‐assessment variation in terminal year biomass and fishing mortality estimates, reference points, relative biomass and fishing mortality estimates, and overfishing limits. There was little evidence of inter‐assessment bias; stock assessment estimates in the terminal year of the assessment were not consistently higher or lower than estimates of the same quantities in future years. However, there was a tendency for extreme values from the terminal year to be pulled closer to the mean in future years. Inter‐assessment variation in all estimates differed across regions, and a longer inter‐assessment interval generally resulted in greater variation. Inter‐assessment uncertainty was greatest for estimates of the overfishing limit, with coefficients of variation ranging from 17% in Europe (non‐EU) to 107% for Pacific Ocean pelagic stocks. Because inter‐assessment variation is only one component of scientific uncertainty, we suggest that these uncertainty estimates may provide a basis for determining the minimum size of precautionary buffers.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Vertical community patterns of Labyrinthulomycetes protists reveal their potential importance in the oceanic biological pump - Mohan Bai; Ningdong Xie; Yaodong He; Jiaqian Li; Jackie L. Collier; Dana E. Hunt; Zackary I. Johnson; Nianzhi Jiao; Guangyi Wang (Environmental Microbiology, 2022)
Summary The biological pump plays a vital role in exporting organic particles into the deep ocean for long‐term carbon sequestration. However, much remains unknown about some of its key microbial players. In this study, Labyrinthulomycetes protists (LP) were used to understand the significance of heterotrophic microeukaryotes in the transport of particulate organic matter from the surface to the dark ocean. Unlike the sharp vertical decrease of prokaryotic biomass, the LP biomass only slightly decreased with depth and eventually exceeded prokaryotic biomass in the bathypelagic layer. Sequencing identified high diversity of the LP communities with a dominance of Aplanochytrium at all depths. Notably, ASVs that were observed in the surface layer comprised ~20% of ASVs and ~60% of sequences in each of the deeper (including bathypelagic) layers, suggesting potential vertical export of the LP populations to the deep ocean. Further analyses of the vertical patterns of the 50 most abundant ASVs revealed niche partitioning of LP phylotypes in the pelagic ocean, including those that could decompose organic detritus and/or facilitate the formation of fast‐sinking particles. Overall, this study presents several lines of evidence that the LP can be an important component of the biological pump through their multiple ecotypes in the pelagic ocean.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic loci underlying quantitative resistance to necrotrophic pathogens Sclerotinia and Diaporthe (Phomopsis), and correlated resistance to both pathogens - Cloe S. Pogoda; Stephan Reinert; Zahirul I. Talukder; Ziv Attia; Erin C. E. Collier-zans; Thomas J. Gulya; Nolan C. Kane; Brent S. Hulke (Theoretical and Applied Genetics, 2021)

The palaeoshoreline of Early Miocene formations (Euphrates and Jeribe) at the periphery of the Zagros Foreland Basin, Sulaimani Governorate, Kurdistan Region, NE Iraq - H. G. Abdullah; R. E. L. Collier; N. P. Mountney (Arabian Journal of Geosciences, 2019)
A sedimentological investigation of the Early Miocene deposits at the periphery of the Zagros Foreland Basin, Kurdistan Region, around Qishlagh-Sargrma and Darbandikhan, reveals the presence of the Euphrates and Jeribe Formations in this area. A carbonate-dominated unit, comprising four regressive carbonate cycles, at the base of the Fatha Formation, has been investigated to characterize the depositional environments and stratigraphic context of these Early Miocene deposits. Outcrop and thin-section analyses of the carbonate succession reveal a gently inclined, carbonate-dominated ramp based on the depositional lithofacies and microfacies. Eight carbonate microfacies were identified and interpreted to have been deposited in a shallow marine environment. The Euphrates Formation passes up from deposits of restricted lagoon to shoal depositional environments, while the Jeribe Formation was deposited in a hypersaline lagoon to a restricted lagoon. The Early Miocene index fossil Borelis melo melo was identified in the deposits of the Euphrates Formation. Stratigraphic correlation of the studied sections allows the development of a revised palaeogeography for the Early Miocene deposits in the Kurdistan Region.

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Finding reference: a comparison of modelling approaches for predicting macroinvertebrate community index benchmarks - J. E. Clapcott; E. O. Goodwin; T. H. Snelder; K. J. Collier; M. W. Neale; S. Greenfield (New Zealand Journal of Marine and Freshwater Research, 2017)
Reference benchmarks are needed to assess the contemporary status of rivers and to establish restoration targets. We developed predictive models to estimate site‐specific reference values for a macroinvertebrate community index (MCI), which is used to indicate a range of human impacts on wadeable streams. We compared three statistical modelling approaches – general linear, boosted regression tree (BRT) and random forest (RF) – and tested the effect of spatial scale on predictive accuracy by developing national and regional BRT models. Using fitted flexible models (BRT, RF) and resetting predictors to reflect natural state provided the most accurate predictions of reference condition. Variation in reference MCI predictions from national and regional models was within the range observed from methodological and temporal variability. The proportion of native vegetation in upstream catchments was the primary predictor of MCI scores in all models, while secondary predictors varied regionally.

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Sequence stratigraphic evolution of The post-rift MEGASEQUENCE in The northern part of The Nile Delta basin, Egypt - Farouk M. El-Fawal; Mohammad A. Sarhan; Richard E. Ll. Collier; Ahmed Basal; Mohammad H. Abdel Aal (Arabian Journal of Geosciences, 2016)

Pro-Inflammatory Interferon Gamma Signaling is Directly Associated with Stroke Induced Neurodegeneration - Hilary A. Seifert; Lisa A. Collier; Cortney B. Chapman; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Journal of Neuroimmune Pharmacology, 2014)

Late Miocene normal faulting beneath the northern Nile Delta: NNW propagation of the Gulf of Suez Rift - Mohammad A. Sarhan; Richard E. Ll. Collier; Ahmed Basal; Mohamed Hamed Abdel Aal (Arabian Journal of Geosciences, 2014)

Decision framework for evaluating the macroeconomic risks and policy impacts of cyber attacks - Andjelka Kelic; Zachary A. Collier; Christopher Brown; Walter E. Beyeler; Alexander V. Outkin; Vanessa N. Vargas; Mark A. Ehlen; Christopher Judson; Ali Zaidi; Billy Leung; Igor Linkov (Environment Systems and Decisions, 2013)

Multiscale approach to the security of hardware supply chains for energy systems - James H. Lambert; Jeffrey M. Keisler; William E. Wheeler; Zachary A. Collier; Igor Linkov (Environment Systems and Decisions, 2013)

Sustainable roofing technology under multiple constraints: a decision-analytical approach - Z. A. Collier; D. Wang; J. T. Vogel; E. K. Tatham; I. Linkov (Environment Systems and Decisions, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Environmental variability during the Last Interglacial: a new high‐resolution pollen record from Tenaghi Philippon, Greece - Alice M. Milner; Ulrich C. Müller; Katherine H. Roucoux; Richard E. L. Collier; Jörg Pross; Stavros Kalaitzidis; Kimon Christanis; Polychronis C. Tzedakis (Journal of Quaternary Science, 2013)
A new high‐resolution Last Interglacial pollen record from the Tenaghi Philippon peatland, northeast Greece, documents variability in forest composition and cover, which we attribute to changes in temperature and moisture availability. The declining stage of the interglacial was marked by a stepwise decrease in temperate tree populations and culminated in the complete collapse of forest at the onset of the ensuing stadial. The coincidence of the onset of the stepwise declining trend with the increased prominence of North Atlantic ice‐rafting events suggests that ecological thresholds in southern Europe were only crossed once ice rafting events intensified, and implies that changes in North Atlantic ocean circulation were an important contributing factor to the declining temperate forest cover in southern Europe. Our results provide evidence for intra‐interglacial variability in the low mid latitudes and suggest a coupling between the high northern latitudes and the northeast Mediterranean during this interval. Copyright © 2013 John Wiley & Sons, Ltd.

A Transient Decrease in Spleen Size Following Stroke Corresponds to Splenocyte Release into Systemic Circulation - Hilary A. Seifert; Aaron A. Hall; Cortney B. Chapman; Lisa A. Collier; Alison E. Willing; Keith R. Pennypacker (Journal of Neuroimmune Pharmacology, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Differential induction of cellular proliferation, hypertrophy and apoptosis in H9c2 cardiomyocytes by exogenous tissue factor - G. Alkistis Frentzou; Mary E. W. Collier; Anne-Marie L. Seymour; Camille Ettelaie (Molecular and Cellular Biochemistry, 2010)

Comparative water balance profiles of Orchidaceae seeds for epiphytic and terrestrial taxa endemic to North America - Jay A. Yoder; Samantha M. Imfeld; Derrick J. Heydinger; Chloé E. Hart; Matthew H. Collier; Kevin M. Gribbins; Lawrence W. Zettler (Plant Ecology, 2010)

Administration of a Sigma Receptor Agonist Delays MCAO-Induced Neurodegeneration and White Matter Injury - Christopher C. Leonardo; Aaron A. Hall; Lisa A. Collier; Suzanne M. Green; Alison E. Willing; Keith R. Pennypacker (Translational Stroke Research, 2010)

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Ultraviolet radiation and bio-optics in Crater Lake, Oregon - B. R. Hargreaves; S. F. Girdner; M. W. Buktenica; R. W. Collier; E. Urbach; G. L. Larson (Hydrobiologia, 2007)

Hyporheic Production is Substantially Greater than Benthic Production for a Common New Zealand Caddisfly - A. E. Wright-Stow; K. J. Collier; B. J. Smith (Hydrobiologia, 2006)

Trophic basis of production for a mayfly in a North Island, New Zealand, forest stream: Contributions of benthic versus hyporheic habitats and implications for restoration - Kevin J. Collier; Aslan E. Wright‐Stow; Brian J. Smith (New Zealand Journal of Marine and Freshwater Research, 2004)
The leptophlebiid mayfly Acantho‐phlebia cruentata (Hudson) is restricted to the North Island and some associated offshore islands of northern New Zealand where it commonly occurs in benthic and hyporheic habitats of forested streams. We investigated: (1) life history; (2) secondary production in benthic and hyporheic habitats; and (3) major energy sources contributing to nutrition and production of this species in a pristine forest stream. Most nymphal size classes were present throughout the year, and emergence extended over several months, peaking from February to April. Despite apparently having extended emergence and recruitment periods, Acanthophlebia exhibited a predominantly univoltine life history. Annual benthic production (calculated by the size‐frequency method) was 0.318 g dry mass (DM) m –2 year –1 , compared to 4.601 g DM m –2 year –1 in high‐density benthic habitats at the tails of pools, and 34.476 g m –3 year –1 for colonisation baskets set at 15–45 cm deep in the substratum. On a habitat weighted basis averaged out over the entire sampling reach, it was estimated that 76% of annual production occurred in hyporheic habitats >10 cm below the streambed surface. Gut contents were dominated by fine particulate matter (FPM) ≤75 μm and larger inorganic material on all dates in individuals from both benthic and hyporheic habitats. Fungi were relatively abundant in guts of benthic animals collected on some dates, whereas spores and pollen were relatively common food items in both habitats on occasions. Analysis of the trophic basis of production, based on gut contents and assumed assimilation and net production efficiencies, indicated that benthic secondary production was supported largely by fungi (48% of production) and FPM (37%), whereas FPM supported a higher level of hyporheic production (52%) than fungi (27%). Although stable carbon isotope values suggested dependence on epilithon, the enriched δ 15 N values for this food source implicated the involvement of a microbial loop whereby a substantial proportion of Acanthophlebia nutrition appeared to be derived from heterotrophs growing in FPM and epilithon that had assimilated dissolved organic carbon. This study has highlighted the significant role that hyporheic habitats can play in the ecology of Acanthophlebia populations in pristine native forest streams. Re‐establishment of hyporheic function would appear to be an important component of stream restoration work to enable the successful recolonisation of Acanthophlebia populations at sites where they historically occurred.

Phenotypic assessment and mapped markers for H31, a new wheat gene conferring resistance to Hessian fly (Diptera: Cecidomyiidae) - C. E. Williams; C. C. Collier; N. Sardesai; H. W. Ohm; S. E. Cambron (Theoretical and Applied Genetics, 2003)

Seasonal Changes in Reproductive Activity in the Potter's angelfish (Centropyge potteri) in Kaneohe Bay, Hawaii - Jason T. Collier; Toyoji Kaneko; Tetsuya Hirano; E. Gordon Grau (Environmental Biology of Fishes, 2003)

A Lectin-Like Wheat Gene Responds Systemically to Attempted Feeding by Avirulent First-Instar Hessian Fly Larvae - Christie E. Williams; Chad C. Collier; Jill A. Nemacheck; Chengzhi Liang; Sue E. Cambron (Journal of Chemical Ecology, 2002)

Biochemical responses to sediment-associated contaminants in brown bullhead (Ameriurus nebulosus) from the Niagara River ecosystem - NANCY A. Eufemia; TRACY K. Collier; JOHN E. Stein; DAVID E. Watson; RICHARD T. Di Giulio (Ecotoxicology, 1997)

Cytoplasmic and mitochondrial arginine kinases inDrosophila: Evidence for a single gene - Lori R. Munneke; Glen E. Collier (Biochemical Genetics, 1988)

Genetic and biochemical characterization of phosphofructokinase from Drosophila melanogaster - Lori R. Munneke; Glen E. Collier (Biochemical Genetics, 1985)

Beiträge zur geographischen Pathologie von Suriname - W. A. Collier; W. E. F. Winckel (Antonie van Leeuwenhoek, 1952)